The Impact of Online Satisfaction and Trust in Building Loyalty: Study on Indonesia E-Commerce Customers - Komariyah, Erna Fitri (IJBLE Scientific Publications Community Inc., 2024)
E-commerce platforms face challenges when it comes to competition that is just a click away. Customers can easily move from one platform to another, so building customer loyalty to establish long-term profitable relationships is necessary. This study investigates the impacts of online satisfaction and trust of e-commerce customers toward loyalty. This study uses data from e-commerce customer respondents in Indonesia who have often shopped online on the Shopee platform. This object is determined to prove that they make repeat purchases through the platform because they feel satisfied and trusted. Respondents vary in age, education, occupation, and income. Thus, the results of this study can be generalized more broadly. A total of 272 respondents were analyzed using SEM with AMOS. The results showed that online satisfaction and trust positively and significantly contribute to loyalty. Furthermore, the most utilized e-commerce benefit by customers is vouchers. Overall, it gives advice for managers to continue to maintain customer loyalty.